Autonomy Orientations of English Language Teachers in Turkey - Aslihan Bagci (National Research University Higher School of Economics, 2021)
The present study aimed to explore autonomy orientations of English language teachers' work at an intensive language school in Turkey. The autonomy orientations of the teachers were analysed through self-determination theory. The study also investigated if these orientations vary according to the teachers' gender, years of experience, and department of graduation. The investigation was carried out through an autonomy orientations questionnaire. Data were collected from 111 language teachers, 11 of whose opinions were utilized for further analysis. The results showed that teachers had moderate autonomy supportive orientation, which was reported to be risky. Moreover, gender was the only variable that had a significant effect on the autonomy orientations. The teachers mainly blamed the education system for restricting their adoption of the autonomous orientations. The results imply the necessity of explicit training on how teachers can be encouraged to have more autonomy supporting orientations.